Self-Regulated Learning in Students Who Pass the SNBT Using E-Learning as a Learning Media - Anastasia, Lois; Abidin, Zainal (GoAcademica Research & Publishing, 2024)
This study explores the effectiveness of self-regulated learning (SRL) in students who pass the SNBT using e-learning as a learning medium. SRL is a process in which students independently manage and maintain their cognitive, emotional, and motivational aspects to achieve predetermined learning goals. Passing the SNBT is an achievement that requires students' learning independence. This research utilized a qualitative method with 4 students who passed the SNBT using e-learning as respondents, selected through convenience sampling. Data were collected through semi-structured interviews, transcribed, and analyzed using thematic analysis. The results of the study indicate that students who used e-learning in SNBT preparation successfully passed the selection and entered the best state universities due to their ability to self-regulate through three phases of SRL: planning, execution, and reflection. E-learning helped students set learning goals, choose appropriate learning strategies, and manage time effectively. During the execution phase, students were active in the learning process and adjusted methods as needed. In the reflection phase, students evaluated learning outcomes and made improvements based on feedback. Students who applied SRL demonstrated high learning independence and motivation. These findings emphasize the importance of integrating technology in education to enhance students' effectiveness and academic success.